Locally Applied Simvastatin as an Adjunct to Promote Spinal Fusion in Rats. Issue 15 (1st August 2019) - Iyer, Sravisht; Donnelly, Patrick E.; Spaniel, George; Young, Kelsey; Oh, Kevin; Cunningham, Matthew E.
Abstract : Study Design: Basic Science. Objective: To determine if locally delivered simvastatin can enhance bone formation in a rat spinal fusion model. Summary of Background Data: The bone-anabolic properties of statins in fracture healing are well established, however, few studies have evaluated the impact of locally delivered statins in spinal fusion. Methods: We formulated poly(lactic-co-glycolic acid) (PLGA) nanoparticles by adapting previously published techniques. Two types of nanoparticles were created: simvastatin nanoparticles (SimNP) and nanoparticles without simvastatin (BlankNP). Drug elution from SimNP was characterized. Osteoblastic differentiation was analyzed using MC3T3-E1 cells cultured in differentiation medium containing SimNP or BlankNP. Forty male 12 week old outbred Wistar rats underwent uninstrumented posterolateral fusion using iliac crest bone graft and BlankNP, SimNP or simvastatin drug. X-rays to assess bone formation were obtained at 4 weeks and 9 weeks post-operatively. Spines were explanted at 9 weeks for micro-CT analysis, and a blinded manual assessment of fusion (MAF). Results: SimNP achieved a release efficiency of 74.1% with ∼50% release occurring in the first day. Simvastatin and SimNP treated cells showed significantly greater expression of osteopontin (OPN) and osteocalcin (OCN). On micro-CT analysis, SimNP animals had higher bone volume and percent bone volume (bone volume/total volume) than control animals. SimNP rats had higher X-ray scores at 4 weeks (p=0.010) and 9 weeks (p<0.001) relative to BlankNP. MAF showed that SimNP had a higher fusion rate than BlankNP (42.9% vs. 0%, p=0.006). Conclusion: We were able to validate that sustained release of simvastatin via a PLGA nanoparticle. SimNP was able to induce an increase in mineralization as well as an increase in markers of bone formation. X-ray analysis, micro-CT quantification, and MAF assessment of SimNP treated rats showed significantly greater bone formation and fusion mass strength relative to vehicle treated animals. Simvastatin may be a safe, cost-effective bone anabolic agent for use in spinal fusion. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the textWe were able to validate the sustained release of Simvastatin via a poly(lactic-co-glycolic acid) nanoparticle. SimNP was able to induce an increase in mineralization and in markers of bone formation in vitro . In a rat spinal fusion model, Sim NP treated animals had significantly greater bone formation and fusion mass strength relative to controls.